Clinical profile of pediatric acute renal failure patients requiring renal replacement therapy age less than 15 years: an ambivalent COHORT study - Solanki, Jayesh R.; Patel, Kishan S. (International Journal of Contemporary Pediatrics, 2024)
Background: Acute kidney injury (AKI) is characterized by a reversible increase in the blood concentration of creatinine and nitrogenous waste products and by the inability of the kidney to regulate fluid and electrolyte homeostasis appropriately. There is minimal data on the clinical profile of pediatric AKI patients age less than 15 years who required renal replacement therapy (RRT). Methods: A total of 301 patients (3%) were diagnosed with AKI, amongst them 66 patients who required RRT from January 2021 to December 2022 were enrolled. Their clinical, biochemical, and etiological profile were studied to find out their influence in modifying the outcome of AKI patients requiring RRT. Results: AKI was noted in 301 patients (3%), amongst them 66 patients we had analyzed who underwent RRT. Result were analyzed in three age group (0-2 month, 2 month-8 year, 8 year-15 year). Male preponderance was seen amongst all age groups with male: female ratio being 2:1, 5:1 and 1.8:1 respectively and rural area preponderance seen in all age groups. Birth asphyxia, neonatal sepsis and septicemia were leading etiologies in different groups. Peritoneal dialysis (PD) was only RRT modality in the 0-2 month age group, while hemodialysis and PD modalities were used in rest groups. Multi-organ dysfunction syndrome was commonly seen comorbidity associated with all groups along with pyogenic meningitis, and encephalopathy. Mortality rate was observed at 47% (n=31). Conclusions: From our study, we conclude that to expand the facility of point of care, hemodialysis facility in ICUs with a larger study or multicentric study in the pediatric age group is required.